A CLINICAL STUDY ON ERANDAMULA KSHEERA BASTI IN THE MANAGEMENT OF VATAJA GRIDHRASI W.S.R TO SCIATICA (International Journal of Ayurveda and Pharma Research, 2019)
Now a day’s large number of population are suffering from low backache because of lifestyle modification, irregular sitting posture and house hold works. Low backache is a common symptom involving the muscles, nerves and vertebral column. Sciatica refers to pain that radiates along the path of Sciatic nerve. It resembles disease “Gridhrasi” in Ayurveda. Radiating pain is the predominant symptom with stiffness, which will hamper the daily activity of an individual. The purpose of the study is to evaluate the efficacy of Erandamula Ksheera Basti in Vataja Gridhrasi. A total 10 patients of Vataja Gridhrasi were administered Erandamula Ksheera Basti in Yoga Basti pattern for 8 days. Vataja Gridhrasi lakshanas and SLR Positive were taken as assessment parameters, which showed significant results. Hence, Erandamula Ksheera Basti has better effect on patients of Vataja Gridhrasi.